2007
DOI: 10.1124/dmd.106.014217
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Oral Drug Absorption of Topotecan through the Inhibition of Intestinal Xenobiotic Efflux Transporter, Breast Cancer Resistance Protein, by Excipients

Abstract: ABSTRACT:Recently, breast cancer resistance protein (BCRP/ABCG2) has been shown to limit the oral absorption of its substrates in the intestine. The purpose of this study was to examine whether excipients can be used as inhibitors of BCRP, to improve the oral drug absorption of BCRP substrates. In wild-type mice, Pluronic P85 and Tween 20, given orally 15 min before topotecan administration, increased the area under the plasma concentration-time curve (AUC) of topotecan after oral administration (2.0-and 1.8-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…There is an additional approach to bypass intestinal efflux by incorporating into oral drug formulations excipients that inhibit Bcrp function. For example, the excipients Pluronic P85 and Tween 20 improve intestinal absorption of the Bcrp substrate topotecan in wildtype but not Bcrp-null mice (Yamagata et al, 2007).…”
Section: Apical Efflux Transporters In Intestinementioning
confidence: 99%
“…There is an additional approach to bypass intestinal efflux by incorporating into oral drug formulations excipients that inhibit Bcrp function. For example, the excipients Pluronic P85 and Tween 20 improve intestinal absorption of the Bcrp substrate topotecan in wildtype but not Bcrp-null mice (Yamagata et al, 2007).…”
Section: Apical Efflux Transporters In Intestinementioning
confidence: 99%
“…ema.europa.eu/docs/en_GB/document_library/Scientific_guideline/ (Zaher et al, 2006) c.34GG and c.421AA/CC/CA: ,2-to 4-fold AUC increases; inconsistent findings between studies (Adkison et al, 2010;Schnepf and Zolk, 2013) No significant association with PK (+dual MDR1/ BCRP inhibitor: pantoprazole) (Adkison et al, 2010); 3.2 max fold AUC increase (+BCRP and enzymes inhibitor: curcumin) (Kusuhara et al, 2012) OATP2B1 substrate (Kusuhara et al, 2012 (Kitamura et al, 2008) c.421CA/AA: 2-to 2.4-fold AUC increases (Zhang et al,. 2006 ;Ieiri et al, 2009;Keskitalo et al, 2009b) 1.6 max fold AUC increase (+ dual OATP/BCRP inhibitors: eltrombopag, ritonavir) (Allred et al, 2011); 7-fold increase (+multiple transporters and enzymes inhibitor: CsA) (Schnepf and Zolk, 2013) (Mizuno et al, 2012); no impact on plasma exposure but on brain distribution (Tang et al, 2012;Schnepf and Zolk, 2013) c.421CA/AA 1.7-to 3-fold AUC increase (Mizuno et al, 2012) (Yamagata et al, 2007) c.421CA: increase in F from ;30% to ;40%, no significant change in AUC, very small sample size (Sparreboom et al, 2005) Increase in F from ;40% to ;100% (+dual MDR1 / BCRP inhibitor: elacridar) (Schnepf a...…”
Section: Introductionmentioning
confidence: 99%
“…ABCG2 mRNA expression was higher compared to other efflux transporter in the human small intestine, which is a rate-limiting barrier to oral drug absorption [64] . The important impact of ABCG2 on the intestinal absorption was further supported by several knockout mice research, which have indicated that ABCG2 affects the pharmacological and toxicological behavior of many drugs [65][66][67] . Also, polymorphisms might influence the role of ABCG2 in intestinal absorption.…”
Section: Breast Cancer Resistance Proteinmentioning
confidence: 91%